Isolation and identification of endophytic fungi from UiTM Reserve Forest, Negeri Sembilan - Siti Nursyazwani Maadon,; Sarini Ahmad Wakid,; Iwana Izni Zainudin,; Lili Syahani Rusli,; Mohd Syahril Mohd Zan,; Nor'Aishah Hasan,; Nor'Aishah Abu Shah,; Emelda Rosseleena Rohani, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Endophytic fungi are those living inside the host plant without causing any apparent negative effect on the host plant. Two isolates endophytic fungi from leaves and two isolates from root at Universiti Teknologi MARA (UiTM) Reserve Forest, Negeri Sembilan were successfully isolated and identified by morphology and molecular characteristic. Samples were surface sterilized and sub-cultured to obtain a pure culture. Characteristics of the isolates such as colony appearance, mycelial texture, conidia/spores and pigmentation were studied to explore their morphology. Isolates were also subjected to a PCR-based genotyping test. There were noticeable differences in morphological characteristics among the four isolates. Microscopic analysis showed four isolates consist of septa and conidia/spores. The pigmentation result showed that colony in A1leaf samples demonstrated an orange color on potato dextrose agar (PDA) media, colony in A1root demonstrate a black texture in PDA media while hairy colonies in the others two isolates showed a white color on PDA media. Based on molecular analyses the fungal genera showed 99-100% similarity with the related fungi recorded in the GenBank. Both morphology and molecular sequencing of internal transcribed spacer (ITS) regions of endophytic fungi showed that three isolates (A1root, C2leaf, and C3root) were grouped in Basidiomycota while one isolate (A1leaf) belonged to Ascomycota. The endophyte funguses were identified as Daldinia sp. (A1leaf), Polyporales sp. (A1root,) Lentinus sp. (C2leaf,) and Rigidoporus sp. (C3root). Overall, the new discoveries of isolated endophyte fungal have dyeing potential of fungal pigments which offer a viable alternative to natural vegetable and harmful synthetic dyes.